What is the clinical and cost-effectiveness of second generation colon capsule endoscopy (CCE-2) compared with optical colonoscopy or CT colonography for the detection of colorectal polyps and cancer in adults with signs or symptoms of colorectal cancer or at increased risk of colorectal cancer?. (2020) - Unknown
No abstract available